Foreign Direct Investment and Unequal Regional Economic Growth in China - Jie Zhang; Gustav Kristensen (European Regional Science Association (ERSA), 1998)
China?s open-door policy has attracted foreign investment to China. The foreign direct investment is unequally distributed in Chinese thirty regions. The regions can be grouped after different critiria: the coastal area, the central area and the western area by geographical critirion, or leaders, followers and outsiders by economical ability to attract foreign investment. The second classification is closely related to the geographical classification. The article discusses the spread of economic growth over the regions as a consequence of the unequal distribution of foreign investment in regions and the consequences in the degree of regional economic inequality. The empirical findings highlight the impact of foreign direct investment on the Chinese regional economies in transition.
Keywords: 330